Efektivitas Penggunaan Tiktok Sebagai Pelestari Tradisi Mitoni Orang Hamil Adat Jawa dalam Wedding Organizer Aksara - Refa Widia Pratiwi; Yuli Kurniati Werdiningsih; Sunarya Sunarya (Journal on Education, 2024)
This research aims to explore the effectiveness of using TikTok as a tool to preserve the Mitoni tradition for pregnant people in the context of Wedding Organizer Aksara. The Mitoni tradition is a Javanese custom which is related to pregnancy and preparation for welcoming the birth of a child. The focus of this research is to discuss the effectiveness of using tiktok as a tool for preserving the Mitoni tradition for pregnant people in Javanese traditional communities, the benefits of this tradition for Javanese traditional communities and what customary sanctions occur if this tradition is violated.